2018
DOI: 10.22478/ufpb.1981-1268.2018v12n3.39306
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação Do Tamanho E Peso De Propágulos Das Espécies Pioneiras De Mangue Na Formação De Plântulas Para a Recuperação De Manguezais

Abstract: As espécies de Laguncularia racemosa e Avicennia schaueriana são pioneiras, importantes no reflorestamento de áreas degradadas de manguezal. Neste contexto, o objetivo deste trabalho foi avaliar o tamanho e peso dos propágulos das espécies Laguncularia racemosa e Avicennia schaueriana na germinação e formação de plântulas mais vigorosas para produção de mudas. O experimento foi conduzido no Instituto Federal do Ceará, localizado no município de Acaraú no estado do Ceará. Em Laboratório, os propágulos passaram … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
1
3
0
2
Order By: Relevance
“…This demonstrated that in deforested areas, the germination potential of L. racemosa can be reduced. Even so, these results corroborate those of other studies where germination tests with L. racemosa propagules resulted in a high germination rate (Silva et al, 2017;Silva and Maia, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This demonstrated that in deforested areas, the germination potential of L. racemosa can be reduced. Even so, these results corroborate those of other studies where germination tests with L. racemosa propagules resulted in a high germination rate (Silva et al, 2017;Silva and Maia, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…The species A. schaueriana and L. racemosa were chosen because they are pioneer mangrove species (Costa et al, 2014). Propagules were collected near the Curral Velho village in the municipality of Acaraú -CE (-2.889037°S and -40.077642°W), according to Silva and Maia (2018). The propagules were collected by manual harvesting, found on the soil, and they were viable and non-germinated.…”
Section: Choice Of Species and Procedures With Propagules Substrate mentioning
confidence: 99%
See 2 more Smart Citations
“…Dados obtidos para o estado do Ceará indicam que as perdas de áreas vegetadas comprometem a dinâmica dentro deste ecossistema afetando o funcionamento de toda a biota e a possibilidade de recuperação (PAULA; LIMA; MAIA, 2016; SILVA, 2018; SILVA; MAIA, 2018). Isso porque, o sombreamento proporcionado pela estrutura do mangue é importante para a garantia da recolonização das espécies, assegurando os processos sucessionais (SILVA, 2018).…”
Section: Impactos Ambientais Em Manguezais No Cearáunclassified